La onomástica de las inscripciones romanas de Segovia. I (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Collection and prior classification of the attested onomastic in the inscriptions of the Roman period in the province of Segovia.
Keywords: Onomastic; Epigraphy; Segovia; Roma